Development and validation of the Chinese version of the conditional reasoning test for implicit aggression in college students - Chu, Kequn; Zhu, Fengshu (Frontiers in Psychology, 2025)
ObjectiveThis study aims to develop an implicit aggression conditional reasoning test suitable for college students and to test its reliability and validity.MethodsBased on an in-depth literature review and expert interviews, the research team identified the theoretical structure of college students’ implicit aggression and the initial items. Through methods such as exploratory factor analysis, confirmatory factor analysis, and reliability and validity testing, the final test scale was formulated and optimized.ResultsThe final implicit aggression conditional reasoning test for college students contained 18 items across six dimensions: hostility attribution bias, target degradation bias, potency bias, revenge bias, oppression bias, and social discounting bias. Confirmatory factor analysis indicated that the scale had good construct validity (χ2 = 333.82, df = 132, RMSEA = 0.08, NFI = 0.91, CFI = 0.92, GFI = 0.90, PGFI = 0.66); the total internal consistency coefficient of the scale was 0.90, and the test-retest reliability was 0.87. The internal consistency coefficients of the subscales ranged from 0.87 to 0.92, with test-retest reliabilities between 0.84 and 0.90. Additionally, the test demonstrated good criterion validity.ConclusionThe development of the implicit aggression conditional reasoning test for college students meets the initial theoretical predictions, and its reliability and validity indicators satisfy the requirements of psychometrics, providing an effective tool for assessing and researching implicit aggression among college students.